Strategic Adaptability in Industrial SMEs Facing Disruption - Mahardika, Rifqi (Journal of Sustainability Industrial Engineering and Management System, 2025)
The ability of small and medium-sized enterprises (SMEs) to strategically adapt to disruptions is a critical determinant of their survival and long-term success. This research investigates the strategic adaptability of industrial SMEs in the face of external disruptions, such as technological advancements, market shifts, and global crises. The primary aim of this study is to examine the key factors influencing strategic adaptability and the strategies employed by industrial SMEs to cope with these challenges. A qualitative research methodology, based on an extensive literature review, was employed to analyze relevant studies and synthesize findings on leadership, organizational culture, innovation, and external disruptions. The research findings indicate that transformational leadership, a culture of innovation, and the adoption of new technologies are central to the strategic adaptability of industrial SMEs. Additionally, the study emphasizes the importance of dynamic capabilities—specifically, the ability to sense, seize, and reconfigure strategies in response to disruptions. The findings suggest that industrial SMEs with strong leadership and adaptive cultures are better equipped to navigate external disruptions and capitalize on emerging opportunities. Moreover, the research highlights the need for SMEs to continuously invest in innovation and develop the flexibility required to adapt to an increasingly volatile and competitive environment. The study’s results provide valuable insights for both academic research and managerial practices, offering a foundation for future studies and practical strategies aimed at enhancing the resilience and adaptability of industrial SMEs.